(untitled) (MAUSAM, 1990)
Using the new JMA operational global model, some prediction experiments were carried out for 1979 and 1986 monsoon onsets. The results of the operational model forecasts for 1988 onset were also examined. In these forecasts, realistic southwesterly monsoon flows developed starting from the pre-onset initial conditions. In most cases, formation and development of synoptic disturbances such as onset vortex and monsoon depressions were also predicted by the model. The accuracy of the prediction of these disturbances, however, varies among the cases.